2013
DOI: 10.3109/09638237.2012.670880
|View full text |Cite
|
Sign up to set email alerts
|

The case for single-session therapy: Does the empirical evidence support the increased prevalence of this service delivery model?

Abstract: Many of the studies have methodological limitations, and future research requires increased use of standardized measures, control groups and larger and more diverse samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
96
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(103 citation statements)
references
References 24 publications
4
96
0
3
Order By: Relevance
“…Two literature reviews were found (Cameron, 2007;Hymmen, Stalker, & Cait, 2013). The purpose of both was to review the literature on single-session therapy, not walk-in mental health services.…”
Section: Existing Reviewsmentioning
confidence: 99%
“…Two literature reviews were found (Cameron, 2007;Hymmen, Stalker, & Cait, 2013). The purpose of both was to review the literature on single-session therapy, not walk-in mental health services.…”
Section: Existing Reviewsmentioning
confidence: 99%
“…A review of single session therapy literature Since Talmon (1990) published Single Session Therapy, a number of other SST reviews have been conducted (Bloom, 2001;Cameron, 2007;Campbell, 2012;Hurn, 2005;Hymmen et al, 2013). In 2001, Bloom concluded that under appropriate therapeutic conditions SST might be effective in achieving a variety of clinical goals.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…This process was guided by: (1) the procedures adopted in other recent critical reviews within sport psychology (e.g., Holt & Tamminen, 2010;Rumbold, Fletcher, & Daniels, 2012); (2) reviews suggesting the integration of new methods into sport psychology from other domains (e.g., Cross, Acquah, & Ramsey, 2014); and (3) previous reviews of SST literature (e.g., Campbell, 2012;Hymmen et al, 2013). Our review will adopt a similar approach in terms of summarizing interventiontype papers; however, given that one of the aims is to provide the reader with an insight into the characteristics and common features of SST that distinguish this way of working from other traditional methods, our review also considers descriptive papers (i.e., overviews, case studies, reflective papers).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…In line with the growing demands for accessibility to mental health services, alongside limited funding for such facilities, single-session therapy (SST) and walk-in SST are becoming popular models of service delivery (Slive, McElheran, & Lawson, 2008). SST, in this sense, refers to a planned single-session intervention approach to problem solving (Hymmen, Stalker, & Cait, 2013;Talmon, 1990).…”
Section: Consultancy Teams In Family Therapymentioning
confidence: 99%
“…Indeed, several descriptive reviews of SST and walk-in SST have concluded that while more experimental research is required in the area, these single-session approaches appear to be effective for a range of problems and can satisfy client expectations (Bloom, 2001;Cameron, 2007;Campbell, 2012;Hymmen et al, 2013). Although the use of a consultancy team is not a universal feature of all single-session therapeutic methods, like other brief methods (e.g., de Shazer, 1985;Selvini & Palazzoli, 1991), it is a characteristic of therapy that is commonplace to the majority of these approaches.…”
Section: Consultancy Teams In Single-session Therapymentioning
confidence: 99%